Formation and Historical Evolution of the Ouled Abdenour Tribe - SEGHIRI , Ahmed (The Algerian Historical Journal, 2026)
The research we propose to undertake focuses on the creation and evolution of the Ouled Abdenour tribe from the Ottoman period up to the French conquest. We first attempted to describe its territory, then examined the history of its founder, and finally, we traced—through a long period (1700–1844) rich in military and political events—the key facts that marked the history of this tribal community.